(untitled) (London Journal of Research In Science: Natural and Formal, 2025)
The study focused on the visibility of websites of agricultural research institutes in Nigeria. A purposive sampling technique was employed to select 34 agricultural research institutes. The specific objectives were to assess the online visibility of these websites and identify the types of agricultural activities showcased. Secondary data were collected using webometric tools such as SEO tools, Moz, Similarweb, and Ahrefs. The research adopted a mixed-method approach, incorporating both quantitative and qualitative data analysis. Quantitative data were analyzed using IBM SPSS (Statistical Package for the Social Sciences), while qualitative data were analyzed using Atlas.ti version 8. The results revealed that the websites of ARMTI, CIFOR, NAERLS, NSPRI, WARDA, FRIN, IFPRI, ICRISAT, NIFOR, NAPRI, NIFST and ICRAF agricultural research institutes had high visibility. The most frequently mentioned words included "research," "food," "capacity," and "development," reflecting the key activities of some agricultural research institutes. Additionally, the coefficient of global rank showed a positive correlation with website visibility, while visit duration and bounce rate exhibited negative correlations. The study concluded that the high and moderate levels of website visibility were associated with the sharing of links and content, as well as maintaining an active presence on social media platforms. It recommended that agricultural research institutes leverage social media platforms such as Twitter, Facebook, and LinkedIn to promote website content and drive traffic, thereby enhancing online visibility and engagement.